2021
DOI: 10.3390/biology10020137
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of the Ag, Cu Nanoparticle System

Abstract: Microbes, including bacteria and fungi, easily form stable biofilms on many surfaces. Such biofilms have high resistance to antibiotics, and cause nosocomial and postoperative infections. The antimicrobial and antiviral behaviors of Ag and Cu nanoparticles (NPs) are well known, and possible mechanisms for their actions, such as released ions, reactive oxygen species (ROS), contact killing, the immunostimulatory effect, and others have been proposed. Ag and Cu NPs, and their derivative NPs, have different antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 290 publications
(400 reference statements)
1
66
0
Order By: Relevance
“…It could also be assumed that the enhanced antimicrobial activity of the bimetallic hybrids of the Au/Cu and Ag/Cu type was caused by the synergistic effect of the coexistence of both metallic species. Similar results were obtained by Fan et al [ 41 ] and Perdikaki et al [ 42 ]. It was shown that AgCu alloys or Ag/Cu-graphene hybrid samples with varied Ag on stainless steel surfaces exhibited higher antimicrobial activity than other tested samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It could also be assumed that the enhanced antimicrobial activity of the bimetallic hybrids of the Au/Cu and Ag/Cu type was caused by the synergistic effect of the coexistence of both metallic species. Similar results were obtained by Fan et al [ 41 ] and Perdikaki et al [ 42 ]. It was shown that AgCu alloys or Ag/Cu-graphene hybrid samples with varied Ag on stainless steel surfaces exhibited higher antimicrobial activity than other tested samples.…”
Section: Discussionsupporting
confidence: 91%
“…As shown by Khare et al, the antibacterial effect of bimetallic surfaces consisting of Ag and Cu is long-term [ 44 ]. A thorough summary of the microstructures and antimicrobial properties of Ag/Cu combinations was presented by Fan et al [ 41 ]. On the other hand, from the electrochemical point of view, the contact of two metals creates a galvanic pair that facilitates the oxidation of the more active component [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, silver nanoparticles are biologically safer and exhibit less toxicity than silver ions. It has been documented that nanoparticle-containing dressings did not produce systemic or local toxicity when applied to nonburn skin wounds (Yamanaka et al, 2005;Marin et al, 2015;Fan et al, 2021). Furthermore, the AgNPs loaded on the carrier can be released continuously and maintain a relatively constant concentration, achieving the purpose of long-lasting antibacterial activity (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we designed and prepared silver nanoparticles (AgNPs) loaded film based on poly (vinyl alcohol) (PVA) and keratin. The crosslinking between PVA and keratin by the action of sodium trimetaphosphate (STMP) provided the film with good mechanical properties to meet the requirements of surgical sutures (Leone et al, 2010;Samoila et al, 2019) while AgNPs conferred excellent antibacterial properties (Xie et al, 2017;Mabrouk et al, 2020;Fan et al, 2021). Furthermore, both in vivo and in vitro experiments were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…By synthesizing Ag/Cu nanoparticles (Ag-CuNPs) and detecting their antibacterial and antifungal activities, Marta et al [89] concluded that Ag-CuNPs exhibited synergistic effects against Escherichia coli, S. aureus, and Candida albicans. Fan et al [90] reported that Ag-CuNPs have a synergistic effect and can significantly enhance the antibacterial properties of alloy nanoparticles. Zhang et al [91] doped Cu ions into a TiO 2 coating on the surface of Ti implants by micro-arc oxidation (MAO) and concluded that TiO 2 -Cu nanoparticles (TiO 2-CuNPs) have good antibacterial ability.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%